THE EFFECT OF WORK TRAINING AND WORK ETHIC ON TEACHER PERFORMANCE THROUGH WORK MOTIVATION AT STATE VOCATIONAL HIGH SCHOOL 1 STABAT - Murti Khairani Lubis; Kiki Farida Ferine; Yohny Anwar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the effect of job training and work ethic on teacher performance with work motivation as a mediating variable at State Vocational High School (SMK) 1 Stabat. The background of the study departs from the importance of improving vocational teacher performance through strengthening training, work ethic, and work motivation. This study uses a quantitative approach with a population of all ASN at SMK Negeri 1 Stabat totaling 89 people (PNS and PPPK), all of whom are used as samples (population research). Data were collected through a Likert scale questionnaire and analyzed using Partial Least Squares (PLS) with SmartPLS. The results showed that job training had a positive but insignificant effect on teacher performance, but a positive and significant effect on work motivation. Work ethic had a positive and significant effect on teacher performance and work motivation. Work motivation also had a positive and significant effect on teacher performance. Indirectly, job training through work motivation did not have a significant effect on teacher performance, while work ethic through work motivation had a positive and significant effect on teacher performance. The R² values of 0.811 for work motivation and 0.862 for teacher performance indicate that the model is able to explain a high proportion of the variance in both dependent variables. This finding confirms that work ethic and work motivation are key factors in improving teacher performance, while on-the-job training plays a greater role in boosting work motivation than directly influencing performance.